Efficient production of renewable hydrocarbon fuels using waste CO2 and green H2 by integrating Fe-based Fischer-Tropsch synthesis and olefin oligomerization. (1st June 2022) - Gao, Ruxing; Zhang, Leiyu; Wang, Lei; Zhang, Chundong; Jun, Ki-Won; Kim, Seok Ki; Park, Hae-Gu; Gao, Ying; Zhu, Yuezhao; Wan, Hui; Guan, Guofeng; Zhao, Tiansheng
Abstract: Recently, Power-to-Liquids (PtL) and Power-to-Gas (PtG) technologies have been regarded as promising pathways for renewable energy storage and CO2 mitigation. Herein, we newly proposed two PtL/PtG hybrid processes (Cases A and B) by integrating the Fe-based Fischer-Tropsch (F-T) synthesis and olefin oligomerization, to further enhance the production of value-added liquid hydrocarbons. The process modelling and case study were implemented to evaluate their process performances by using Aspen Plus. In addition, the effects of different feeding conditions (i.e., CO/CO2 feeding) and process configurations (i.e., F-T synthesis only or two-stage reactor) were also comparatively analyzed. It is found that both Cases A and B are efficient technologies for converting CO2 into value-added hydrocarbons, and Case A is found to be more beneficial in the aspects of the carbon and thermal efficiencies, and net CO2 reduction. While, Case B is competitive in producing high-value liquid hydrocarbons. Moreover, the options of CO2 feeding and two-stage reactor are more preferable than the options of CO feeding and F-T synthesis only, and both Cases A and B are more competitive in the aspects of syncrude production, thermal efficiency, and CO2 reduction, as compared to the Base cases 1–3. Highlights: Two PtL/PtG hybrid process options are proposed for CO2 transformation. F-T synthesis and olefin oligomerization are integrated in the proposed PtL/PtG processes. A comparative analysis of the present and previous PtL/PtG processes are conducted. The present PtL/PtG processes are technically more competitive than the previous ones.